Human capital accumulation, technological progress, and corporate financialization - Dong, Zixuan; Abd Aziz, Mohd Faiq; Wang, Yan (Elsevier Inc., 2025)
This study selects data from listed companies between 2008 and 2022 as the research sample, delving into the interrelationships among human capital accumulation, technological progress, and corporate financialization. The empirical results indicate the following: First, human capital accumulation promotes corporate financialization. Second, technological progress also facilitates the process of corporate financialization. Moreover, technological progress serves as a mediating factor in the relationship between human capital accumulation and corporate financialization. Additionally, the impact of human capital accumulation on corporate financialization shows no significant difference between state-owned enterprises (SOEs) and private enterprises (PEs). Similarly, the effect of technological progress on corporate financialization does not exhibit notable differences between SOEs and PEs. Finally, the influence of human capital accumulation on corporate financialization demonstrates a scale threshold effect.